1970
DOI: 10.1088/0031-8949/1/5-6/008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Isomeric 29/2+ Level in 211At

Abstract: A 70 ns isomeric state at 2 641 keV has been produced in the 209Bi(α,2n)211 At reaction and interpreted as the 29/2+ state of the h 9/2 2 i 13/2 proton configuration. It decays to the states (h 9/2 2 f 7/2)23/2, (h 9/2 3)21/2, (h 9/2 3)17/2, (h 9/2 3)13/2 and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 3 publications
4
12
0
Order By: Relevance
“…The relative intensities of the delayed gamma rays are given in Table 3 a. It should now be observed that this scheme suggests the following intensity relation of delayed gamma rays: [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30](1 + ~) =11.536 +11,438 +I1,1 54.+11.252 =/tot" Since none of the high energy gamma rays can have a higher multipolarity than E3, the conversion electron intensities can be neglected. From Table 3a it is found that:…”
Section: B) Transitions Indicating the 27/2-levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative intensities of the delayed gamma rays are given in Table 3 a. It should now be observed that this scheme suggests the following intensity relation of delayed gamma rays: [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30](1 + ~) =11.536 +11,438 +I1,1 54.+11.252 =/tot" Since none of the high energy gamma rays can have a higher multipolarity than E3, the conversion electron intensities can be neglected. From Table 3a it is found that:…”
Section: B) Transitions Indicating the 27/2-levelmentioning
confidence: 99%
“…Previously we have investigated high spin levels in 2nAt (Ref. 17) and 2~ (Ref. 18), which correspond to three protons and two neutron holes plus a proton, respectively.…”
Section: Comparison Between Experimental and Calculated Energiesmentioning
confidence: 99%
“…In the odd-A At isotopes, 29/2 + isomeric states have been observed [11][12][13][14][15]. They are assigned to the π (i 13/2 h 2 9/2 ) configuration.…”
Section: Bandmentioning
confidence: 94%
“…The structure of the isomer is associated with the coupling of an h 9/2 proton to the 12 + isomeric state in the 192 Pb core. In several odd-A At isotopes, isomeric states with a spin and parity of 29/2 + have been identified [11][12][13][14][15] and associated with the coupling of the h 9/2 proton to the π (h 9/2 i 13/2 ) configuration. Moreover, the search for highly excited superdeformed (SD) bands to better understand the nuclear properties under extreme deformation has turned out to be very successful in this region of the nuclear chart [8,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…8 two-particle cases: 2~ [1], 2~ 2~ 2~ 21~ 21~ 21~ [2], and 2~ 12 three-particle cases: 2~ [3] , 2~ 2~ 2~ 2~ 2~ 211pb, mBi, 211Po, 211At [4], 2~ [5], and 2~ [6] and 16 four-particle cases: 2~ [7], 2~ 2~ 2~ 2Ogpt, 2~ ' 2~ ' 21~ ' 212pb ' 2tZBi ' 212p0 ' 212At ' 212Rn, 21~ [8], 2~ [9], 2~…”
Section: ~mentioning
confidence: 99%